2016
DOI: 10.1002/prca.201600074
|View full text |Cite
|
Sign up to set email alerts
|

Serum protein profiling in diffuse large B‐cell lymphoma

Abstract: These preliminary data when combined with other cancer-related data regarding these proteins warrant continued research in clinical and large prospective studies to clarify the role for these biomarkers in DLBCL pathogenesis and/or prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…ECM1 can regulate M1 macrophage polarization through the granulocyte-macrophage colony-stimulating factor/ STAT5 signaling pathway in in ammatory bowel disease (IBD) 16 . It has also been reported that ECM1 was statistically signi cantly elevated in diffuse large B-cell lymphoma patient sera as compared to controls 17 . Here we report that ECM1 is also involved in B-ALL.…”
Section: Discussionmentioning
confidence: 82%
“…ECM1 can regulate M1 macrophage polarization through the granulocyte-macrophage colony-stimulating factor/ STAT5 signaling pathway in in ammatory bowel disease (IBD) 16 . It has also been reported that ECM1 was statistically signi cantly elevated in diffuse large B-cell lymphoma patient sera as compared to controls 17 . Here we report that ECM1 is also involved in B-ALL.…”
Section: Discussionmentioning
confidence: 82%
“…The mass spectrometric analysis of hippocampal proteins was done as previously described 31 . Briefly, using a split flow configuration, peptide digests were injected into a dSurveyor HPLC plus (Thermo Fisher Scientific, MA, USA) and data were collected in CID mode.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed procedure of host cell protein extraction and digestion was described in previous publications [18, 19]. In brief, the host cell proteins were first extracted from cell pellets using M-PER, denatured and run into a 10% SDS Bis-Tris PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…LC-MS/MS was applied to acquire the high-quality peptide precursor and fragment ion data as described in literature [19]. Each proteomics sample was injected to LC-MS/MS with triplication.…”
Section: Methodsmentioning
confidence: 99%